Clidicostigus gen. nov., the first Mesozoic genus of Mastigini (Coleoptera: Staphylinidae: Scydmaeninae) from Cenomanian Burmese amber. (April 2017) - Jałoszyński, Paweł; Brunke, Adam J.; Metscher, Brian; Zhang, Wei-Wei; Bai, Ming
Abstract: The Mastigitae is a small supertribe of ant-like stone beetles that currently includes nine extant and five extinct genera. Extinct taxa are known within tribes Clidicini and Mastigini; the latter with one genus discovered in Baltic amber. For the first time, a Mesozoic genus of the tribe Mastigini is described, Clidicostigus arachnipes Jałoszyński, Brunke and Bai, gen. et sp. nov., from Cenomanian Burmese amber. The new taxon shares an enlarged and spiny scape and pedicel with its extant relatives but has deep elytral grooves and a strongly elongate and asymmetrical maxillary palpomere IV; the beetle has also enormously elongate maxillary palps and legs. The elongation of appendages in combination with only moderately large eyes is postulated to have evolved as an adaptation to running quickly, with tactile and chemical senses predominating over sight. The mode of life of Clidicostigus might have been similar to that of extant Mastigini, especially of particularly slender South African species that run on the ground and climb bushes and trees in search of prey. Highlights: The oldest known extinct genus unambiguously placed in Mastigini is described from Cretaceous Burmese amber. Clidicostigus arachnipes gen. & sp. nov. is extremely elongate and has elytral striae, not known in extant Mastigini. Five out of nine extant tribes of Scydmaeninae are currently known from the Cretaceous.